SUPPLIER MANAGEMENT BASED ON PERFORMANCE INDICATORS: A STUDY IN THE PULP AND PAPER SECTOR - Viebrantz, Gabriel; Milnitz, Diego (Seven Editora, 2025)
Supplier management is one of the strategic pillars for the competitiveness of supply chains, especially in highly productive sectors such as pulp and paper. In an environment characterized by deverticalization, an increasing number of partners, and pressures for efficiency and sustainability, performance indicators become essential tools to evaluate and align expectations between customers and suppliers. This article aims to analyze the use of performance indicators in supplier management in the pulp and paper sector in Santa Catarina, highlighting their contribution to reliability and continuous improvement of the supply chain. Methodologically, the research is exploratory, with both quantitative and qualitative approaches, developed through a literature review and the application of a structured questionnaire to 36 companies, obtaining 30 valid responses. The results show that the most valued indicators are delivery time, quality, and cost, although aspects such as flexibility, production capacity, after-sales service, and socio-environmental responsibility also emerge as relevant criteria. It was found that the systematic application of indicators contributes to greater reliability, enhances communication among partners, and enables joint action plans for continuous improvement. Additionally, established suppliers in the market tend to achieve better performance, reinforcing the importance of accumulated experience and long-term partnerships. As a contribution, the study broadens the understanding of the application of performance indicators in a strategic sector, emphasizing the need to incorporate emerging dimensions such as innovation and sustainability in the evaluation and development of suppliers.DOI: https://doi.org/10.56238/sevened2025.029-109